Higher Reliability of Electric Power Supply under Wind Electrical Installation Operation in General Power System by Optimization of Their Scheduled Control Period - Y. A. Rolik; A. V. Gornostay (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2010)
The paper considers reliability criteria characterizing wind electrical installations (WEI) as restorable systems. It has been shown that the main criterion influencing on reliability of WEI electric supply is a restoration time. Evaluation of restoration time influence on WEI control time has been made in the paper. The paper presents methodology for determination of optimum period  of  WEI control. The optimum period of the scheduled control for WEI of NORDEX-type No.54 has been determined in the paper.